Transformasi Pembangunan Jalan Tol Indonesia Melalui Kepemimpinan Basuki Hadimuljono - Indri Valensia Rahmadhani; Maulani Subandari Arjun; Dela .; Nafra Maulia Rifa; Ibdia Zikra; Yulia Hanoselina (CV. ITTC INDONESIA, 2026)
Toll road development has become one of the Indonesian government's strategic efforts to improve regional connectivity and support national economic growth. During the period of 2014–2024, toll road development experienced significant acceleration under the leadership of the Minister of Public Works and Public Housing (PUPR), Basuki Hadimuljono. This study aims to analyze the transformation of toll road development in Indonesia through the perspective of transformational leadership. The study adopts Bass’s transformational leadership theory, which consists of four dimensions: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. A qualitative approach was employed using the Systematic Literature Review (SLR) method. Data were collected through documentation studies of scientific journal articles, academic books, and relevant government documents. The selected literature was analyzed thematically to identify patterns and relationships between transformational leadership and infrastructure development outcomes. The findings indicate that the acceleration of toll road development was supported by regulatory reforms, innovative financing schemes, and transformational leadership practices that strengthened inter-agency coordination and facilitated the resolution of development challenges. Furthermore, the leadership approach contributed to the successful implementation of infrastructure policies and the expansion of the national toll road network. The study concludes that transformational leadership played a significant role in supporting the successful transformation of toll road development in Indonesia during the period under review.